(untitled) (International Journal of Biology and Chemistry, 2018)
Wheat is a major cereal crop for both human and animal nutrition, providing 28 % of the world’s edible dry matter and up to 60 % of the daily calorie intake in developing countries. Across years, wheat breeding reduced its genetic diversity by replacing traditional cultivars with modern higher yielding varieties and this has resulted in decreased nutritional quality. Spring wheat genetically stable mutant lines (M7 generation) produced on genetic background of cv. Eritrospermum-35 after 100 and 200 Gy gamma treatments to broaden genetic variation and search for new resources were analyzed for grain protein content and nutritionally important protein fractions (albumins, globulins and prolamins). A significant positive correlation between grain protein content and yield-associated traits, such as grain number and weight per spike, were observed in the 100- and 200 Gy-dosed mutant lines with different means, r2 =0.141, (p<0.05) and r2 =0.068, (p<0.05), respectively. Albumins ranged from 139.5 to 890.4 μ g/g, globulins – from 130.1 to 344.04 μ g/g. The 200 Gy-dosed M7 mutant lines showed the highest globulins concentration by 1.84 fold higher, compared to cv. Eritrospermum-35. Prolamins level varied from 65.1 to 398.2 μ g/g in mutant lines. High dose of irradiation (200 Gy) generated higher level of variation, when compared to 100 Gy. ANOVA analysis revealed significant variation (p<0.05) in globulins and prolamins. In order to improve both quantity and quality of wheat proteins and influence selection of improved raw materials for the flour and bread-making industry a more detailed knowledge of the variability of grain proteins and protein fractions accumulation among new spring wheat mutant lines varieties could be useful. In addition, to improve whole-wheat flour application in production of functional food, rich in health-beneficial components, the study of the whole grain proteins content, their structure and quality is significant.